Anomalous course of the sigmoid colon and the mesosigmoid encountered during colectomy. A case report of a redundant loop of sigmoid colon. (2018) - Zarokosta, Maria; Piperos, Τheodoros; Zoulamoglou, Menelaos; Theodoropoulos, Panagiotis; Nikou, Euthumios; Flessas, Ioannis; Boumpa, Eleni; Bonatsos, Vasileios; Noussios, George; Mariolis-Sapsakos, Theodoros
Highlights: A redundant sigmoid colon is defined as one that is too long to fit into its owner's body without undergoing reduplication. It is associated with acute and chronic pathological conditions, sigmoid volvulus and serious confusions in radiological diagnosis and instrumentation of imaging procedures. Surgeons, obstetricians and radiologists ought to be aware of this variation and to emphasize to the correlation between gross and clinical anatomy, since their awareness determines the outcomes of an operation and the accurate radiographic diagnosis. Abstract: Introduction Sigmoid colon constitutes a part of the large intestine that presents several congenital anatomic variations. In particular, the presence of a redundant loop of sigmoid colon is of tremendous importance for surgeons, obstetricians and radiologists, since it is closely related to multiple pathological conditions and functional implications of the neighboring anatomical structures. Presentation of case: An unusual anatomic variation in position and length of the sigmoid colon and its mesocolon was unexpectedly detected during right hemicolectomy to a 67-year-old Caucasian male patient due to colon cancer. The operation was uneventful. A meticulous review of the literature was conducted as well. Discussion: A redundant loop of sigmoid colon may go unnoticed or it might lead to urinary, digestive and vascular complications. Its presence is associated with acute and chronic pathological conditions, sigmoid volvulus and serious confusions in radiological diagnosis and instrumentation. Conclusion: Surgeons' thorough knowledge concerning this rare anatomic variation is fundamental and crucial in order to establish a correct diagnosis and assert the appropriate management when performing operations including pelvis and abdomen.